MUTASI GEN Kat G PADA ISOLAT KLINIS R2 FENOTIPE MULTI DRUG RESISTEN Mycobacterium Tuberculosis - Pane, Elfira Rosa (Universitas Islam Negeri Raden Fatah, 2012)
Tuberculosis (TB) is an infected diseased caused by Mycobactenum tuberculosis, and tiratmeni with anti-tuberciulosis drugs (OAT) could cuird the disease. Inappopriate medication could cause TB drugs resistance. Multi-drug Resistant TB (MDR-TB) describes strains of tuberTrulosis that are resistant to at least the two main first line TB drugs - isoniajd (INH) and rifamticin (R1F), (World Health Orgariation). The am of our researth is to find the genotipe information about The caused of resistece INH in clinical isolate R2. The methods used in our research is Polymertuse Chain Reaction (PCR) muhiplex specific alleles kat G and electroporesis gel agarose all isolates produced two multiplex PCR 0,43kb and 0,29kb bands. Sequencing produce electroforegnim 0,43kb frament gene katG compared to the same frment M. tuberculosis wild tipe. Homology analsis showed isolate R2 have mutation in nucleotide 869, C to T. Data anasis obtained here thowed that C869T mutation in isolate R2 located in codon 290, GCT change in to GTT, and the consequence is amino acid alanin replaced by valin. Pymol program show amino acid residue 290 located in loop region N terminal and attmximately from the actize site. The effect of this mutation and the relation in resistance INH bar no yet known. The implication of our results is to give the new information about mutation position in kat G gene M tuberculosis which is resistance INH because of mutation C869T (alanin29Ovalin) in isolate R2 hate not been published before.